Security Enhancement in Wireless Sensor Network using Sagacity Dismissal of Conquered Movements - Anithaashri, T.P.; Rajendran, P.Selvi; G.Ravichandran, (International Journal of Psychosocial Rehabilitation, 2020)
Wireless Sensor Network (WSN) is a new approach for network programmability, which refers to the ability to control, change, and manage network behavior dynamically through sensor via open interfaces in contrast to relying on closed boxes and proprietary defined interfaces. It envision the plan, deploy the critical service, performance and industrial management upgrades for the utilization of 5th generation technology. The WSN framework enables centralized control of data path elements independently of the network technology used to connect these devices that can originate from different vendors. The centralized control embeds all the intelligence and maintains a network wide view of the data path elements and links that connect them. This sensor based network makes the controller suitable to perform network management functions while allowing easy modifications to the networking functions through the centralized control plane. To meet the vast requirements it is mandatory to enhance the technology in the network application, for which the software defined network can be very essential to meet the challenges in the technical advancement for rendering and utilizing the services. The overhead of the additional virtual nodes diminishes as network size increases, which has consistent improvement in enhancing the security in the transactions of data on large networks.